Using Lego® Bricks to Build a Growth Mindset: A Case Study. Issue 2 (3rd April 2023) - O'Sullivan, David; Baxter, Eric
Abstract: This case study illustrates how building with Lego® bricks was used to help an athlete identify instances of growth mindset in his play such that this could help him overcome fix mindset thinking. The player, a member of a trophy winning hurling squad, was self-motivated and had developed a strategy of saying, "No" to avoid becoming injured due to 'over playing'. He participated in a Lego® Serious Play® in Positive Psychology group workshop, the theme of which was the growth mindset. As a result, he was able to determine how he could work from fixed mindset triggers to more growth mindset beliefs. He was then able to transform his thinking from a stance where he felt he had to protect himself from the demands of others to realizing they can contribute to him as he developed as a player. He reported that building with Lego® bricks helped him "form new ideas in ways that you wouldn't be able to do just through your mind". This report demonstrates how a growth mindset workshop which incorporated Lego® Bricks can support player development after the experience adverse circumstances.